Konstruksi sosial pernikahan beda agama dikalangan Muslim Tionghoa di Probolinggo - M. Hasyim Syamhudi (Ijtihad : Jurnal Wacana Hukum Islam dan Kemanusiaan, 2011)
The reciprocal connection between religion and family life makes the topic of religious intermarriage ofparticular importance in the sociology of religion. This study was conducted to examine social phenom-ena of interreligious marriage which become popular among Moslems Chinese society in Probolinggo.The main purpose of this study will try to find, why Moslems Chinese society in Probolinggo performinterfaith marriage, which was all the long associated to be forbiden in both Islamic legal system andpossitive common law of Indonesia. In this research the researcher has difficulties to get proper infor-mation about religious behavior, especially about interfaith marriage problems. To solve this problem,the researcher asked for help from the leader of Persatuan Imam Tauhid Indonesia (PITI) Probolinggo,Mr. Irem Grok Sing to get access to main informans.This qualitative research used Berger’s theory ofsocial reconstruction process to explain phenomena. Interreligious marriage as a social discordance inProbolinggo Chinese Moslem community was predicted will expand faster. So there was need somedialogue between religious ideal concepts. In Islamic law, this phenomena can be understood as anactualization of the rahmatan li al-‘alamin mission.